MICROSOFT ACCESS AS A SUPPORT SYSTEM IN NEW STUDENT RECEPTION SMA NEGERI 1 Curug Tanggerang - Dhandy Aprisar; Sahni Damerianta Purba, Skom., MMSI Sahni Damerianta Purba, Skom., MMSI (Jurnal Sistem Informasi, 2004)
The rapid computer developments lately almost cover all areas of life one of them is a computer or computer usage in educational institutions. The development of personal computers (PCs) are becoming more sophisticated and faster process but with a smaller form than the initial findings so that price is becoming more affordable and easily obtainable.Suggested advantage is that it can save time, effort and accuracy of the data more reliable, but still there are still perceived shortage is the lack of experts who understand the software that is used is when there hamabatn obstacles and interference.